(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article discusses the main directions in the development of the modern telecommunications market. An analysis of the trends in digitalization of the global economy and the activities of world leaders in the field of information technology, the introduction of patented devices and the 5G network to the market were also carried out.